Preparation of delafossite-based quantum dot hole transport material and application of delafossite-based quantum dot hole transport material in solar cell

By using copper-iron semiconductor quantum dot CuBO2-X material as the hole transport layer in perovskite solar cells, the problem of poor conductivity of the hole transport layer in perovskite solar cells is solved, the photovoltaic performance and stability are improved, and the photovoltaic performance and stability are promoted. The industrial application of perovskite solar cells.

CN119143178APending Publication Date: 2024-12-17ANHUI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411346999.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

The existing perovskite solar cell hole transport layer materials have poor conductivity, which affects device performance and stability, and limits the photovoltaic performance and commercial application of perovskite solar cells.

Method used

CuBO2 is prepared by regulating the reaction of Cr(NO3)3·9H2O or Ga(NO3)3·9H2O, Cu(NO3)2·3H2O, NaOH and HX. -X quantum dots, combined with hydrothermal method and ultrasonic treatment, form CuBO2-X thin films with high conductivity and excellent carrier mobility, used in the trans structure of perovskite solar cells.

Benefits of technology

It improves the photovoltaic performance and stability of perovskite solar cells, enhances the binding force with the perovskite interface, inhibits ion migration, extends the service life of the device, and promotes its industrialization development.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119143178A_ABST
    Figure CN119143178A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of solar cells, and discloses a novel hole transport material based on delafossite CuBO2-X semiconductor quantum dots and a preparation method of a perovskite solar cell containing the material. The material comprises quantum dots which are formed by CuBO2-X and have the diameter of 1-5 nm and the thickness of 1-10 nm, and a layer of compact thin film is formed by the quantum dots and serves as a hole transport layer of a perovskite solar cell. As the hole transport material has the characteristics of proper energy level structure, high conductivity and the like, extraction and transmission of current carriers are facilitated, in addition, the hole transport material is good in chemical stability and wide in band gap, the hole transport material is applied to a trans-perovskite solar cell as a hole transport layer, the layer can absorb very strong ultraviolet light, and the hole transport material can be applied to the solar cell. Therefore, the perovskite film is effectively prevented from being degraded due to irradiation of strong ultraviolet light, ion migration can be inhibited due to the fact that the interface characteristic is enhanced, the device shows higher stability, and therefore the efficient and stable perovskite solar cell can be obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solar cells. More specifically, it relates to a novel delafossite semiconductor quantum dot CuBO 2 -X material preparation and solar cell containing such material as hole transport layer and preparation method thereof. Background Art

[0002] In recent years, with the rapid development of social economy, the demand for energy has been growing, but the reserves of traditional non-renewable energy have decreased sharply, and its use will cause a series of environmental problems. Therefore, it is necessary to find a clean energy to replace traditional energy. Among them, solar energy is the most ideal renewable energy among many clean energy sources. It is inexhaustible, so the development and utilization of solar energy is of great significance to solving the sustainable development of human society and energy shortage problems. Perovskite solar cells have excellent photoelectric properties such as high absorption coefficient, long carrier lifetime, adjustable band gap and high carrier mobility. At the same time, their preparation process is simple and the cost of raw materials is low. They have always been a research hotspot in the field of solar cells. Perovskite solar cells are mainly divided into two types: formal (nip) and trans (pin) structures, specifically including transparent conductive glass substrate, electron / hole transport layer, perovskite light absorption layer, hole / electron transport layer, and metal electrode. As a key functional layer of perovskite solar cells, the hole transport layer mainly collects and transports holes to achieve effective separation of electrons and holes, while protecting the perovskite layer from external erosion by water, oxygen, and light, which has an important impact on the efficiency and stability of the cell. However, commonly used organic hole transport layer materials such as Spiro-OMeTAD have problems such as low hole mobility and conductivity, PTAA has problems such as poor conductivity and hydrophobicity, and commonly used inorganic hole transport layer materials such as NiO x It can only be used in trans (pin) devices, and its hole transport capacity is not ideal. Based on this, the further improvement of the photovoltaic performance and stability of perovskite solar cells and their commercial application are limited. Therefore, designing a new type of stable hole transport layer to enhance the carrier extraction and transport capabilities, thereby improving the efficiency and stability of perovskite solar cells, is of great significance to the industrial development of perovskite solar cell devices. Summary of the invention

[0003] The purpose of the present invention is to solve the problem that the common hole transport layer of current perovskite solar cells has inherent limitations such as poor conductivity, which in turn affects the performance of the device, and to provide a perovskite solar cell based on delafossite semiconductor quantum dot material and a preparation method thereof, as well as a long-term, efficient and stable perovskite solar cell containing the material as a hole transport layer and a preparation method thereof.

[0004] The delafossite semiconductor quantum dot material has the characteristics of suitable energy level structure, high conductivity and excellent carrier mobility, and the halogen ligand can passivate the uncoordinated Pb 2+ , thereby effectively reducing interface defects and enhancing the bonding force with the perovskite interface. Using it as a hole transport material for perovskite solar cells can improve the photovoltaic performance of the device. In addition, the delafossite quantum dot material has good chemical stability and a wide band gap. It is used as a hole transport layer in an inverted perovskite solar cell. This layer can absorb strong ultraviolet light, thereby effectively preventing the perovskite film from being degraded by strong ultraviolet light. The enhanced interface characteristics can inhibit ion migration, and the device exhibits higher stability. Therefore, by using the delafossite semiconductor quantum dot material as a hole transport layer, a long-term, efficient and stable perovskite solar cell can be obtained, accelerating its industrial development.

[0005] In order to achieve the above object, the present invention provides a novel delafossite semiconductor quantum dot material, which comprises CuBO 2 -X forms quantum dots with a diameter of 1~5 nm and a thickness of 1~10 nm.

[0006] Another aspect of the present invention provides a novel delafossite semiconductor quantum dot (CuBO 2 -X) A method for preparing the material, the method comprising the following steps: Weigh a certain amount of chromium nitrate nonahydrate (Cr(NO 3 ) 3 9H 2 O) or gallium nitrate nonahydrate (Ga(NO 3 ) 3 9H 2 O) powder and copper nitrate trihydrate (Cu(NO 3 ) 2 ·3H 2 O) powder was added with a certain volume of deionized water (H 2 O), stirring to obtain a uniformly mixed solution; Weigh a certain amount of sodium hydroxide (NaOH) powder and add it to the above mixed solution, and continue stirring for a while; Add a certain volume ratio of oleic acid and ethanol solution into the above mixed solution and continue stirring for a period of time; The obtained solution was transferred to a reactor and subjected to hydrothermal reaction at 240°C for 8 h; The obtained dark green precipitate was washed several times with n-hexane and anhydrous ethanol and then dispersed in n-hexane for further use; Take a certain volume of the above product in n-hexane solution, add a certain proportion of hydrofluoric acid, hydrochloric acid, hydrobromic acid or hydroiodic acid in ethanol, ultrasonicate for a period of time and then centrifuge to collect the solid, which is CuBO 2 -X (B = Cr, Ga) (X = F, Cl, Br, I) quantum dots are finally dispersed in N,N-dimethylformamide (DMF).

[0007] Another aspect of the present invention also provides a CuBO 2 -X (B = Cr, Ga) (X = F, Cl, Br, I) thin film preparation method, the method comprising the following steps: CuBO 2 -X (B=Cr, Ga) (X=F, Cl, Br, I) delafossite semiconductor material is dispersed in an organic solvent to obtain a dispersion, wherein the delafossite semiconductor material comprises CuBO 2 -X (B = Cr, Ga) (X = F, Cl, Br, I) formed quantum dots with a diameter of 1~5 nm and a thickness of 1~10 nm.

[0008] The above dispersion was spin-coated to form CuBO 2 -X (B=Cr, Ga) (X=F, Cl, Br, I) thin film layer.

[0009] In another aspect, the present invention provides a solar cell, wherein the structure of the solar cell comprises, from bottom to top, a transparent conductive substrate, a hole transport layer, a perovskite layer, an electron transport layer, a buffer layer and an electrode layer, wherein the hole transport layer comprises CuBO 2 -X (B = Cr, Ga) (X = F, Cl, Br, I) delafossite semiconductor material thin film layer, the delafossite semiconductor material contains CuBO 2 -X (B = Cr, Ga) (X = F, Cl, Br, I) formed quantum dots with a diameter of 1~5 nm and a thickness of 1~10 nm.

[0010] Preferably, the perovskite layer is ABX 3 ,A=CH 3 NH 3 NH 2 CHN 2 , Cs or a mixture thereof; B=Pb or Sn or a mixture thereof; X=I, Br, Cl, CN, SCN or a mixture thereof.

[0011] In another aspect, the present invention provides a method for preparing the solar cell, the method comprising the following steps: preparing a transparent conductive substrate; forming a hole transport layer on the transparent conductive substrate; forming a perovskite layer on the hole transport layer; forming an electron transport layer on the perovskite layer; forming a buffer layer on the electron transport layer; forming an electrode layer on the buffer layer; Wherein, the hole transport layer comprises CuBO 2 -X (B = Cr, Ga) (X = F, Cl, Br, I) delafossite semiconductor material thin film layer, the delafossite semiconductor material contains CuBO 2 -X forms quantum dots with a diameter of 1~5 nm and a thickness of 1~10 nm.

[0012] In another aspect, the present invention provides a solar cell, wherein the structure of the solar cell comprises, from bottom to top, a transparent conductive substrate, an electron transport layer, a perovskite layer, a hole transport layer and an electrode layer, wherein the hole transport layer comprises CuBO 2 -X thin film layer of delafossite semiconductor material, the delafossite semiconductor material comprising CuBO 2 -X forms quantum dots with a diameter of 1~5nm and a thickness of 1~10nm.

[0013] Preferably, the perovskite layer is ABX 3 ,A=CH 3 NH 3 NH 2 CHN 2 , Cs or a mixture thereof; B=Pb or Sn or a mixture thereof; X=I, Br, Cl, CN, SCN or a mixture thereof.

[0014] In another aspect, the present invention provides a method for preparing the solar cell, the method comprising the following steps: preparing a transparent conductive substrate; forming an electron transport layer on the transparent conductive substrate; forming a perovskite layer on the electron transport layer; forming a hole transport layer on the perovskite layer; forming an electrode layer on the hole transport layer; Wherein, the hole transport layer comprises CuBO 2 -X (B = Cr, Ga) (X = F, Cl, Br, I) delafossite semiconductor material thin film layer, the delafossite semiconductor material contains CuBO 2 -X forms quantum dots with a diameter of 1~5 nm and a thickness of 1~10 nm.

[0015] Beneficial Effects The present invention regulates Cr(NO 3 ) 39H 2 O or Ga (NO 3 ) 3 9H 2 O, Cu(NO 3 ) 2 ·3H 2 Preparation of CuBO from O, NaOH and HX (X = F, Cl, Br, I) 2 -X (B = Cr, Ga) (X = F, Cl, Br, I) quantum dot materials, the CuBO 2 -X quantum dot material is dispersed in DMF, and the obtained dispersion is spin-coated on a transparent conductive substrate to form a thin film as a hole transport layer of an inverse perovskite solar cell.

[0016] Delafossite semiconductor quantum dots CuBO 2 -X materials are used as hole transport materials for inverse perovskite solar cells because of their suitable energy level structure, high conductivity and excellent carrier mobility. The ligand Cl can passivate the uncoordinated Pb 2+ , thereby effectively reducing interface defects and strengthening the bonding with the perovskite buried interface, thus improving the photovoltaic performance of the device. 2 -X has good chemical stability and a wide enough band gap, and the device exhibits stronger light stability, because CuBO 2 -X layer can absorb strong ultraviolet light, thus effectively preventing the perovskite film from being degraded by strong ultraviolet light. And the enhanced interface characteristics can inhibit ion migration, and the device shows higher stability. Therefore, the use of the delafossite semiconductor quantum dots (CuBO 2 -X) materials as hole transport layers can obtain efficient and stable perovskite solar cells. BRIEF DESCRIPTION OF THE DRAWINGS The above and other objects, features and other advantages of the present invention will be more clearly understood from the following detailed description taken in conjunction with the accompanying drawings, in which: Figure 1 The CuCrO prepared in Example 1 is shown 2 - Transmission electron microscopy image of Cl quantum dots; Figure 2 The schematic diagram of the structure of the solar cell device of Example 5 of the present invention is shown, wherein 1 is a transparent conductive substrate, 2 is an electron transport layer, 3 is a perovskite layer, 4 is a hole transport layer and 5 is an electrode layer; Figure 3 A schematic diagram of the structure of a solar cell device according to Example 6 of the present invention is shown, wherein 1 is a transparent conductive substrate, 2 is a hole transport layer, 3 is a perovskite layer, 4 is an electron transport layer, 5 is a buffer layer and 6 is an electrode layer.

[0017] Figure 4The JV characteristic curve of the perovskite solar cell SC-2 prepared in Example 6 of the present invention is shown; Figure 5 A maximum output power stability test graph of the perovskite solar cell SC-2 prepared in Example 6 of the present invention under a simulated standard sunlight intensity is shown. DETAILED DESCRIPTION

[0018] The present application provides a novel delafossite semiconductor quantum dot CuBO 2 -X materials used as hole transport layers in perovskite solar cells.

[0019] The novel delafossite semiconductor quantum dot material CuBO provided in this application 2 -X forms quantum dots with a diameter of 1 to 5 nm and a thickness of 1 to 10 nm. By controlling the size of the quantum dots within the above range, the CuBO 2 -Thin films made of X quantum dot materials can be suitable for perovskite solar cells.

[0020] The new type of copper iron ore CuBO used in this application 2 -X semiconductor quantum dot material preparation method is: (1) Weigh a certain amount of chromium nitrate nonahydrate (Cr(NO 3 ) 3 9H 2 O) or Ga (NO 3 ) 3 9H 2 O powder and copper nitrate trihydrate (Cu(NO 3 ) 2 ·3H 2 O) powder was added with a certain volume of deionized water (H 2 O), stirring to obtain a uniformly mixed solution①; (2) Weigh a certain amount of sodium hydroxide (NaOH) powder and add it to the above mixed solution ①, and continue stirring for 10 minutes to obtain solution ②; (3) Add a certain volume ratio of oleic acid and ethanol solution into the above mixed solution ② and continue stirring for 10 min to obtain solution ③; (4) Immediately transfer solution ③ to a reactor and perform a hydrothermal reaction at 240°C for 8 hours; (5) After the reaction, the obtained dark green precipitate was washed several times with n-hexane and anhydrous ethanol and then dispersed in n-hexane for further use; (6) Take a certain volume of the n-hexane solution of the above product, add a certain proportion of HX (X = F, Cl, Br, I) ethanol solution, add an appropriate amount of methanol after ultrasonic treatment for 2 h, and then centrifuge at 10000 rpm for 3 min to collect the solid, which is the delafossite semiconductor quantum dot CuBO 2 -X material; (7) CuBO 2 -X quantum dot material is dispersed in DMF to obtain a dispersion for use, and the delafossite semiconductor material comprises CuBO 2 -X forms quantum dots with a diameter of 1-5 nm and a thickness of 1-10 nm.

[0021] Using the CuBO of this application 2 -X quantum dot materials can prepare a new type of CuBO 2 -X thin film, the thin film electrode comprises the CuBO 2 -X quantum dot material and used as a hole transport layer in perovskite solar cells. 2 The thickness of the -X hole transport layer is 1-10 nm, preferably 1-5 nm. Controlling the thickness of the hole transport layer within the above range can ensure the effective extraction of charges in the device. 2 -X has a suitable energy level structure and high conductivity, and the ligand halogen can passivate the interface defects of the perovskite film and strengthen the bonding with the perovskite interface, thereby improving the photovoltaic performance of the device. 2 -X has good chemical stability and wide band gap. It is used as a hole transport layer in inverse perovskite solar cells. This layer can absorb strong ultraviolet light and effectively prevent the perovskite film from being degraded by strong ultraviolet light. The enhanced interface characteristics can inhibit ion migration and the device shows higher stability. Therefore, by using the delafossite semiconductor quantum dots CuBO 2 -X materials are used as hole transport layers in perovskite solar cells to obtain efficient and stable perovskite solar cells. The specific performance parameters of perovskite solar cells are shown in Table 1 below: .

[0022] According to some embodiments of the present application, CuBO 2 The -X hole transport layer can be prepared by the following method: 2-X quantum dot material is dispersed in an organic solvent to obtain a dispersion, and the dispersion is formed into a thin film by spin coating. Preferably, the dispersion can be formed using one or more organic solvents selected from DMF, n-butylamine or ethanol. This method for preparing a hole transport layer has a simple process, does not require expensive equipment and complex conditions, is convenient for device assembly, and is conducive to the commercial production of perovskite solar cells.

[0023] Using delafossite semiconductor quantum dots CuBO 2 -X material hole transport layer, some embodiments of the present application provide a solar cell, the structure of the solar cell includes from bottom to top: a transparent conductive substrate, an electron transport layer, a perovskite layer, a hole transport layer and an electrode layer, wherein the hole transport layer comprises CuBO 2 -Thin film layer of X quantum dot material.

[0024] Preferably, the perovskite layer is ABX 3 ,A=CH 3 NH 3 NH 2 CHN 2 , Cs or a mixture thereof; B=Pb or Sn or a mixture thereof; X=I, Br, Cl, CN, SCN or a mixture thereof.

[0025] Preferably, the transparent conductive substrate is FTO conductive glass or ITO conductive glass.

[0026] Preferably, the electron transport layer is a dense TiO 2 layer, more preferably, the dense TiO 2 The layer thickness is 40~100nm.

[0027] Preferably, the thickness of the perovskite layer is 300-500 nm.

[0028] Preferably, the hole transport layer is CuBO 2 -X thin layer, more preferably, the hole transport layer has a thickness of 1 to 10 nm.

[0029] Preferably, the electrode layer is Au or Ag, and more preferably, the electrode layer has a thickness of 60-100 nm.

[0030] The above-mentioned CuBO 2 -X quantum dot hole transport layer solar cells can be prepared by the following method: preparing a transparent conductive substrate; forming an electron transport layer on the transparent conductive substrate; forming a perovskite layer on the electron transport layer; forming a hole transport layer on the perovskite layer; forming an electrode layer on the hole transport layer; Wherein, the hole transport layer comprises CuBO 2 -X thin film layer of delafossite semiconductor material, the delafossite semiconductor material comprising CuBO 2 -X forms quantum dots with a diameter of 1~5 nm and a thickness of 1~10 nm.

[0031] More specifically, the step of preparing the transparent conductive substrate may be a step of cleaning the transparent conductive substrate. For example, the FTO or ITO conductive glass substrate may be cleaned in an ultrasonic cleaner. More preferably, the substrate may be cleaned in sequence with weak alkaline liquid detergent having a pH of 8 to 10, deionized water, acetone, and anhydrous ethanol for 5 to 20 minutes each. Cleaning the transparent conductive substrate may be performed using other methods that can be used in the art.

[0032] The step of forming an electron transport layer on the transparent conductive substrate can be performed by spraying a solution of an organic titanium source on the transparent conductive substrate and heating the organic titanium source, for example, isopropyl titanate. More specifically, for example, a cleaned FTO conductive glass substrate can be heated at 400-600° C., and a 0.01-0.05 mol / L isopropyl titanate isopropanol solution can be sprayed on the substrate and heated for 20-60 minutes to form a 40-100 nm thick dense TiO 2 Electron transport layer.

[0033] The perovskite layer, preferably the perovskite material is as mentioned above, and can be ABX 3 , where A=CH 3 NH 3 NH 2 CHN 2 , Cs or a mixture thereof; B=Pb or Sn or a mixture thereof; X=I, Br, Cl, CN, SCN or a mixture thereof. More specifically, a 1.0-1.5 mol / L perovskite solution is deposited on a substrate by a one-step or two-step spin coating method, and heated at 100-150 °C for 0.5-1 h to form a 200-1000 nm perovskite active layer.

[0034] The hole transport layer is CuBO 2 -X quantum dot dispersion was spin-coated on the perovskite layer and heated. More specifically, a CuBO 2 The DMF dispersion of -X is spin-coated on the perovskite layer and heated at 50-100 °C for 10-60 minutes to form a 1-10 nm thick CuBO 2 -X hole transport layer. As mentioned above, the CuBO 2-X quantum dot dispersion can be prepared by mixing the CuBO 2 -X quantum dot material is dispersed in an organic solvent. Preferably, one or more organic solvents selected from DMF, n-butylamine or ethanol can be used to form a dispersion.

[0035] The electrode layer can be formed by evaporating Au or Ag on the hole transport layer by vacuum coating. More specifically, the thickness of the electrode is controlled by regulating the evaporation speed and evaporation time of Au or Ag, thereby forming an electrode layer with a thickness of 40 to 200 nm.

[0036] Utilizing CuBO 2 -X hole transport layer. Other embodiments of the present application also provide a solar cell, whose structure includes, from bottom to top: a transparent conductive substrate, a hole transport layer, a perovskite layer, an electron transport layer, a buffer layer and an electrode layer.

[0037] Among them, the preparation of the transparent conductive substrate, the hole transport layer, the perovskite layer, the electron transport layer and the electrode layer has been described in detail above and will be omitted here.

[0038] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. If no specific technology or conditions are indicated in the embodiments, the technology or conditions described in the literature in this area or the product instructions are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially. The term "and / or" used herein includes any and all combinations of one or more related listed items.

[0039] Example 1: Novel delafoscite semiconductor quantum dots (CuCrO 2 Preparation of -Cl) materials: Prepare CuCrO as follows: 2 -Cl quantum dots: (1) Weigh a certain amount of chromium nitrate nonahydrate (Cr(NO 3 ) 3 9H 2 O) powder and copper nitrate trihydrate (Cu(NO 3 ) 2 ·3H 2 O) powder was added with a certain volume of deionized water (H 2 O), and stirred to obtain a uniformly mixed solution①.

[0040] (2) Weigh a certain amount of sodium hydroxide (NaOH) powder and add it to the above mixed solution ①. Continue stirring for 10 minutes to obtain solution ②.

[0041] (3) Add oleic acid and ethanol solutions in a certain volume ratio into the above mixed solution ② and continue stirring for 10 min to obtain solution ③.

[0042] (4) Immediately transfer solution ③ to a reactor and conduct a hydrothermal reaction at 240°C for 8 h.

[0043] (5) After the reaction, the obtained dark green precipitate was washed with n-hexane and anhydrous ethanol several times and then dispersed in n-hexane for further use.

[0044] (6) Take a certain volume of the n-hexane solution of the above product, add a certain proportion of hydrochloric acid ethanol solution, add an appropriate amount of methanol after ultrasonic treatment for 2 h, and then centrifuge at 10000 rpm for 3 min to collect the solid, which is the delafossite semiconductor quantum dot CuCrO 2 -Cl materials.

[0045] Example 2: Novel delafossite semiconductor quantum dots (CuCrO 2 Preparation of -Br) materials: Prepare CuCrO as follows: 2 -Br quantum dots: (1) Weigh a certain amount of chromium nitrate nonahydrate (Cr(NO 3 ) 3 9H 2 O) powder and copper nitrate trihydrate (Cu(NO 3 ) 2 ·3H 2 O) powder was added with a certain volume of deionized water (H 2 O), and stirred to obtain a uniformly mixed solution①.

[0046] (2) Weigh a certain amount of sodium hydroxide (NaOH) powder and add it to the above mixed solution ①. Continue stirring for 10 minutes to obtain solution ②.

[0047] (3) Add oleic acid and ethanol solutions in a certain volume ratio into the above mixed solution ② and continue stirring for 10 min to obtain solution ③.

[0048] (4) Immediately transfer solution ③ to a reactor and conduct a hydrothermal reaction at 240 °C for 8 h.

[0049] (5) After the reaction, the obtained dark green precipitate was washed with n-hexane and anhydrous ethanol several times and then dispersed in n-hexane for further use.

[0050] (6) Take a certain volume of the n-hexane solution of the above product, add a certain proportion of hydrobromic acid ethanol solution, add an appropriate amount of methanol after ultrasonic treatment for 2 h, and then centrifuge at 10000 rpm for 3 min to collect the solid, which is the delafossite semiconductor quantum dot CuCrO 2 -Br material.

[0051] Example 3: Novel delafoscite semiconductor quantum dots (CuGaO 2 Preparation of -Cl) materials: Prepare CuGaO as follows: 2 -Cl quantum dots: (1) Weigh a certain amount of gallium nitrate nonahydrate (Ga(NO 3 ) 3 9H 2 O) powder and copper nitrate trihydrate (Cu(NO 3 ) 2 ·3H 2 O) powder was added with a certain volume of deionized water (H 2 O), and stirred to obtain a uniformly mixed solution①.

[0052] (2) Weigh a certain amount of sodium hydroxide (NaOH) powder and add it to the above mixed solution ①. Continue stirring for 10 minutes to obtain solution ②.

[0053] (3) Add oleic acid and ethanol solutions in a certain volume ratio into the above mixed solution ② and continue stirring for 10 min to obtain solution ③.

[0054] (4) Immediately transfer solution ③ to a reactor and conduct a hydrothermal reaction at 240 °C for 8 h.

[0055] (5) After the reaction, the obtained precipitate was washed with n-hexane and anhydrous ethanol several times and then dispersed in n-hexane for further use.

[0056] (6) Take a certain volume of the n-hexane solution of the above product, add a certain proportion of hydrochloric acid ethanol solution, add an appropriate amount of methanol after ultrasonic treatment for 2 h, and then centrifuge at 10000 rpm for 3 min to collect the solid, which is the delafossite semiconductor quantum dot CuGaO 2 -Cl materials.

[0057] Example 4: Novel delafoscite semiconductor quantum dots (CuGaO 2 Preparation of -Br) materials: Prepare CuGaO as follows: 2 -Br quantum dots: (1) Weigh a certain amount of gallium nitrate nonahydrate (Ga(NO 3 ) 3 9H2 O) powder and copper nitrate trihydrate (Cu(NO 3 ) 2 ·3H 2 O) powder was added with a certain volume of deionized water (H 2 O), and stirred to obtain a uniformly mixed solution①.

[0058] (2) Weigh a certain amount of sodium hydroxide (NaOH) powder and add it to the above mixed solution ①. Continue stirring for 10 minutes to obtain solution ②.

[0059] (3) Add oleic acid and ethanol solutions in a certain volume ratio into the above mixed solution ② and continue stirring for 10 min to obtain solution ③.

[0060] (4) Immediately transfer solution ③ to a reactor and conduct a hydrothermal reaction at 240 °C for 8 h.

[0061] (5) After the reaction, the obtained precipitate was washed with n-hexane and anhydrous ethanol several times and then dispersed in n-hexane for further use.

[0062] (6) Take a certain volume of the n-hexane solution of the above product, add a certain proportion of hydrobromic acid ethanol solution, add an appropriate amount of methanol after ultrasonic treatment for 2 h, and then centrifuge at 10000 rpm for 3 min to collect the solid, which is the delafossite semiconductor quantum dot CuGaO 2 -Br material.

[0063] Example 5: Preparation of perovskite solar cell SC-1: According to the following steps, the Figure 2 The perovskite solar cell SC-1 of the device structure shown includes a transparent conductive substrate, an electron transport layer, a perovskite layer, a hole transport layer and an electrode layer distributed from bottom to top: (1) Cleaning of conductive glass: First, scrub the surface of the FTO conductive glass substrate with a diluted solution of a weak alkaline liquid detergent, and then ultrasonically clean it with deionized water, acetone, and anhydrous ethanol for 15 min each; (2) Preparation of electron transport layer: The treated FTO conductive glass substrate was placed on a heating table and heated at 500 °C for 10 min. Then, a 0.05 mol / L isopropyl titanate solution was sprayed on the substrate. After that, it was placed on a heating table and annealed for 20 minutes to form a dense TiO2 layer with a thickness of about 60 nm. 2 Electron transport layer; (3) Preparation of perovskite layer: A 1.4 mol / L perovskite precursor solution was prepared according to a certain ratio, and 50 uL of the prepared perovskite precursor solution was spin-coated on the above-mentioned electron transport layer. The spin-coating parameters were 5000 rpm for 30 s, and 100 uL of anti-solvent chlorobenzene was evenly and quickly dripped at the 5th second before the end of the spin coating. After the spin coating was completed, the perovskite active layer was placed on a heating table at 100 °C for annealing for 40 minutes to obtain a perovskite active layer. (4) Preparation of hole transport layer: Prepare 10 mg / mL CuCrO 2 -Cl dispersion in DMF was spin-coated on the perovskite active layer at 3000 rpm for 30 s and heated on a heating table at 100 °C for 10 min to obtain a 5 nm hole transport layer; (5) Preparation of electrode layer: The half-cell prepared in the above steps is placed in a vacuum evaporator and evaporated under high vacuum conditions to obtain a 100 nm thick Au electrode layer. After completing the above steps, the perovskite solar cell SC-1 is obtained.

[0064] Example 6: Preparation of perovskite solar cell SC-2: According to the following steps, the Figure 3 The perovskite solar cell SC-2 of the device structure shown in the figure includes, from bottom to top, a transparent conductive substrate, a hole transport layer, a perovskite layer, an electron transport layer, a buffer layer and an electrode layer: (1) Cleaning of conductive glass: First, scrub the surface of the FTO conductive glass substrate with a diluted solution of a weak alkaline liquid detergent, and then ultrasonically clean it with deionized water, acetone, and anhydrous ethanol for 15 min each; (2) Preparation of hole transport layer: The treated FTO conductive glass substrate was placed on a heating table and heated at 500 °C for 10 min, and then the prepared 10 mg / mL CuCrO 2 -Cl dispersion in DMF was spin-coated on this substrate at 3000 rpm for 30 s and heated on a heating table at 100 °C for 10 min to obtain a 5 nm dense hole transport layer; (3) Preparation of perovskite active layer: A 1.4 mol / L perovskite precursor solution was prepared according to a certain ratio, and 50 uL of the prepared perovskite precursor solution was spin-coated on the above-mentioned hole transport layer. The spin-coating parameters were 5000 rpm for 30 s, and 100 uL of anti-solvent chlorobenzene was evenly and quickly dripped at the 5th second before the end of the spin coating. After the spin coating was completed, the solution was placed on a heating table for annealing at 100 °C for 40 minutes to obtain a perovskite active layer. (4) Preparation of electron transport layer: Use anhydrous chlorobenzene to prepare a PCBM solution with a concentration of 25 mg / mL, and spin-coat it on the perovskite active layer. The spin-coating parameters are 3000 rpm for 30 seconds. After annealing at 70°C for 10 minutes, a 60 nm thick electron transport layer is obtained. (5) Preparation of buffer layer: Dissolve an excess of BCP material in anhydrous ethanol, take 70 uL of the supersaturated solution and spin-coat it on the electron transport layer at 6600 rpm for 30 s, then anneal on a heating table at 70 °C for 10 min to obtain a buffer layer with a thickness of 20 nm; (6) Preparation of electrode layer: The half-cell prepared in the above steps is placed in a vacuum evaporator and evaporated under high vacuum conditions to obtain a 100 nm thick Au electrode layer. After completing the above steps, the perovskite solar cell SC-2 is obtained.

[0065] The SC-2 was placed under a standard solar simulator for testing, as shown in Table 1 and Figure 3 As shown, it contains delafossite semiconductor quantum dots CuCrO 2 -Cl material as the hole transport layer of the inverse perovskite solar cell, has a better photoelectric performance. 2 -Cl material (here the conventional hole transport material PTAA is used) in Example 6, the open circuit voltage of the battery device SC-2 is 1.11 V and the short circuit current is 24.26 mA / cm 2 , the filling factor is 81.80%, the photoelectric conversion efficiency is 22.02%, and the CuCrO 2 -Cl hole transport material, the battery device SC-2 in Example 6 has an open circuit voltage of 1.15 V and a short circuit current of 25.48 mA / cm 2 , the filling factor is 83.11%, and the photoelectric conversion efficiency is 24.35%. The test results show that CuCrO 2 -Cl quantum dot materials as hole transport layers significantly improve the open circuit voltage and photoelectric conversion efficiency of perovskite solar cell devices. 2 -Cl has the characteristics of suitable energy level structure, high conductivity and excellent carrier mobility, and the ligand Cl can passivate the uncoordinated Pb in the perovskite light absorption layer. 2+ , strengthening the bonding with the buried perovskite interface, thereby effectively reducing interface defects and thus improving the photovoltaic performance of the device.

[0066] In addition, according to Figure 5 The stability test results show that without using CuCrO 2-Cl inverse perovskite solar cell device efficiency has begun to decrease after 200 h of operation, while the CuCrO 2 -Cl as the hole transport layer of the device SC-2 still maintains an efficiency of more than 80% after 1600 h of illumination with a single sun intensity. The test conditions are that the device is packaged and in a nitrogen atmosphere. The above data results show that due to CuCrO 2 -Cl has good chemical stability and a wide band gap. It is used as a hole transport layer in inverse perovskite solar cells. This layer can absorb strong ultraviolet light and effectively prevent the perovskite film from being degraded by strong ultraviolet light. The enhanced interface characteristics can inhibit ion migration and the device shows higher stability. Therefore, the new delafossite semiconductor quantum dots (CuCrO 2 -Cl) materials as hole transport layers can obtain efficient and stable perovskite solar cells, providing new ideas for subsequent research and its commercial development.

[0067] The above description is a detailed description of the preferred feasible embodiments of the present invention, but the embodiments are not intended to limit the scope of the patent application of the present invention. All equivalent changes or modified changes completed under the technical spirit suggested by the present invention should fall within the patent scope covered by the present invention.

Claims

1. A method for preparing a novel delafossite semiconductor quantum dot CuBO2-X material, wherein B is one of Cr and Ga, and X is one of F, Cl, Br, and I, characterized in that: The preparation method of the novel delafossite semiconductor quantum dot CuBO2-X material comprises the following steps: Weigh a certain mass of chromium nitrate nonahydrate (Cr(NO3)3·9H2O) or gallium nitrate nonahydrate (Ga(NO3)3·9H2O) powder and copper nitrate trihydrate (Cu(NO3)2·3H2O) powder, add a certain volume of deionized water (H2O), and stir to obtain a uniformly mixed solution; Weigh a certain amount of sodium hydroxide (NaOH) powder and add it to the above mixed solution, and continue stirring for a while; Add a certain volume ratio of oleic acid and ethanol solution into the above mixed solution and continue stirring for a period of time; The obtained solution was transferred to a reactor and subjected to hydrothermal reaction at 240°C for 8 h; The obtained dark green precipitate was washed several times with n-hexane and anhydrous ethanol and then dispersed in n-hexane for further use; Take a certain volume of n-hexane solution of the product, add a certain proportion of ethanol solution of hydrofluoric acid, hydrochloric acid, hydrobromic acid or hydroiodic acid, ultrasonicate for a period of time and then centrifuge to collect the solid, which is CuBO2-X quantum dots, and finally disperse it in N,N-dimethylformamide (DMF); The new delafossite semiconductor quantum dot CuBO2-X material is a quantum dot with a diameter of 1~5 nm and a thickness of 1~10 nm.

2. A solar cell, characterized in that: The structure of the solar cell includes, from bottom to top, a transparent conductive substrate, a hole transport layer, a perovskite layer, an electron transport layer, a buffer layer and an electrode layer. The hole transport layer is a thin film layer of a novel delafossite semiconductor quantum dot CuBO2-X material. The novel delafossite semiconductor quantum dot CuBO2-X material is a quantum dot with a diameter of 1 to 5 nm and a thickness of 1 to 10 nm. B is one of Cr and Ga, and X is one of F, Cl, Br and I.

3. The solar cell according to claim 2, characterized in that: The perovskite layer is ABX3, A=CH3NH3, NH2CHNH2, Cs or a mixture thereof; B=Pb or Sn or a mixture thereof; X=I, Br, Cl, CN, SCN or a mixture thereof.

4. A method for preparing the solar cell according to claim 3, characterized in that: The method comprises the following steps: preparing and processing transparent conductive glass substrates; forming a hole transport layer on the transparent conductive substrate; forming a perovskite layer on the hole transport layer; forming an electron transport layer on the perovskite layer; forming a buffer layer on the electron transport layer; forming an electrode layer on the buffer layer; Among them, the hole transport layer is a thin film layer of a new type of delafossite semiconductor quantum dot CuBO2-X material, and the new type of delafossite semiconductor quantum dot CuBO2-X material is a quantum dot with a diameter of 1~5 nm and a thickness of 1~10 nm.

5. A solar cell, characterized in that: The structure of the solar cell includes, from bottom to top, a transparent conductive substrate, an electron transport layer, a perovskite layer, a hole transport layer and an electrode layer, wherein the hole transport layer is a thin film layer of a novel delafossite semiconductor quantum dot CuBO2-X material, the novel delafossite semiconductor quantum dot CuBO2-X material is a quantum dot with a diameter of 1 to 5 nm and a thickness of 1 to 10 nm, B is one of Cr and Ga, and X is one of F, Cl, Br and I.

6. The solar cell according to claim 5, characterized in that: The perovskite layer is ABX3, A=CH3NH3, NH2CHNH2, Cs or a mixture thereof; B=Pb or Sn or a mixture thereof; X=I, Br, Cl, CN, SCN or a mixture thereof.

7. A method for preparing a solar cell according to claim 6, characterized in that: The method comprises the following steps: preparing a transparent conductive substrate; forming an electron transport layer on the transparent conductive substrate; forming a perovskite layer on the electron transport layer; forming a hole transport layer on the perovskite layer; forming an electrode layer on the hole transport layer; Among them, the hole transport layer is a thin film layer of a new type of delafossite semiconductor quantum dot CuBO2-X material, the new type of delafossite semiconductor quantum dot CuBO2-X material is a quantum dot with a diameter of 1~5 nm and a thickness of 1~10 nm, B is one of Cr and Ga, and X is one of F, Cl, Br, and I.